PERAN PEER GROUP EDUKASI DALAM PENINGKATAN PENGETAHUAN KONSEP DIRI REMAJA DI PANTI ASUHAN - Ike Mardiati Agustin; Dwiana Febriyanti; Sawiji Sawiji (Jurnal Ilmu Keperawatan Jiwa, 2018)
TTHE ROLE OF PEER GROUP EDUCATION FOR INCREASING KNOWLEDGE OF THE SELF ESTEM ORPHANGE ADOLESCENT eenagers are someone in the stage of seeking identity to support the formation of self-concept. Teenagers who experience changes in self-concept need a way to develop their own concepts. Peer group education is one way that can be done to support the process of developing self-concept. Aims This study aims to determine the role of peer group education in developing adolescent self-concept of Orphanage X in Kebumen District. Method This study uses quasi experimental design method with one group pree test and post test design approach with 29 total respondents consisting of 2 male peer group groups totaling 18 respondents and 11 female peer group respondents. The education process in the peer group was given for 4x meetings for each group with each meeting held for 90 minutes, the instruments used were questionnaires, modules and evaluation formats. Result The results showed that there was an influence of the role of the peer education group in increasing the knowledge of adolescent self-concept X orphanage in Kebumen District with a p value (0,000)> 0.05. The formation of this educational peer group is recommended not only to improve adolescent self-concept of orphanages but also for adolescents in general.